DEFLECTION BEHAVIOR OF THE NAILED SLAB SYSTEM-SUPPORTED EMBANKMENT ON PEAT SOIL - Waruwu, Aazokhi; Hardiyatmo, Hary Christady; Rifa’i, Ahmad (Journal of Applied Engineering Science, 2017)
Peat is one of the most problematic sub-soil foundation. It had high compressibility, low shear strength, and excessive and long-term settlement when subjected to imposed loads of construction. The efficient method for improvement of peat was preloading. It consists of applying a load in the form of the embankment. One of the alternatives for supported embankment construction was the use of nailed-slab system. A small-scale model laboratory research and settlement analysis were conducted to identify the effectiveness of nailed-slab system in reducing peat settlement due to the embankment. The research results indicated that the installation of piles on slabs was able to reduce the settlement of slabs and increase the modulus of sub-grade reaction. The performance of piles and slab were monolithically connected, it was more effective than non-monolithic piles.